Comparative Study of Business Promotion - Ramadhan, A H; Aria, M (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to find out the influence and the benefits of the website in business promotion. In this study, we used a comparative research method about the advantages of business promotion using a web site compared to business promotion using conventional media. The comparison between promotion through the website and conventional media methods are done in terms of cost, speed of information updating, area of information distribution, and detailed information. The results showed the advantages of promotion using website media compared to conventional media in terms of cost, speed of updating information, the breadth of information distribution, and detailed information. In conclusion, it can be used for business people to determine the marketing strategy.